Randomised, blinded, placebo controlled trial of doxycycline for chronic seronegative arthritis. Issue 12 (1st December 2001) - Smieja, M; MacPherson, D W; Kean, W; Schmuck, M L; Goldsmith, C H; Buchanan, W; Hart, L E; Mahony, J B
Abstract : OBJECTIVE: To determine whether long term doxycycline improves symptoms in patients with chronic seronegative or reactive arthritis. METHODS: A randomised, triple blind, controlled clinical trial of three months' treatment with doxycycline or placebo of patients with chronic reactive or seronegative arthritis was conducted. The primary study end points were three month pain and functional status measured by a self administered Arthritis Impact Measurement Scales version 2 (AIMS2) quality of life questionnaire. Secondary end points were pain and functional status at 6–12 months, three month rheumatologist assessed joint count, pain, and arthritis activity, and treatment efficacy in those with previous exposure to chlamydia. RESULTS: Of 60 patients randomly allocated to receive doxycycline or placebo, results from 37 were evaluable at three months. Groups were well balanced for major prognostic variables. Doxycycline had no detectable effect at three months on pain change scores (mean difference 1.5, 95% CI −1.2 to 4.2, p=0.25) or composite functional change scores (mean difference 0.8, 95% CI −5.6 to 7.1, p=0.81). Furthermore, there were no differences in secondary study end points, and no apparent treatment effect in patients with previous chlamydia infection. CONCLUSION: Three months' treatment with doxycycline did not improve pain or functional status in patients with chronic reactive or seronegative arthritis.